Agent-Based Management for Intermediary Service Provider - Ivaschenko, Anton; Syusin, Ilya; Fedosov, Anton (2014 IEEE/WIC/ACM International Joint Conferences on Web Intelligence (WI) and Intelligent Agent Technologies (IAT), 2014)
In this paper there is introduced a solution for Intermediary Service Provider management based on network optimization and multi-agent technologies. Special attention is given to considering a combination of time factor and human factor in subject-oriented processes of decision making support.